TATA NILAI DAN MODAL SOSIAL DALAM RANGKA PENANGGULANGAN KEMISKINAN PERDESAAN DI JAWA TENGAH - Mursid Zuhri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
This study aims to (a) study the role of social capital in poor fishing activities, (b) studying Social Network Community fishermen, (c) institutional study - institutions that are built primarily a fishing community empowerment and economic institutions (d) to formulate and develop a model description institutional development for the empowerment of the poor fishermen on the south coast and the northern coast of Central Java.The results showed that (a) natural capital (natural capital) in eleven villages of coastal and marine samples, the majority of formal education did not complete elementary school and low income. (b) a smooth interaction between authorities and unions supported the social relations based on ties of neighborhood, kinship, and religious (c) The villages that have the most powerful social capital is the village of Tasikagung, followed by the Village Klidang Lor, Celong Kedawung, Pasir and Karangduwur. In the rural communities that have a relatively strong social capital is likely to be high levels of public welfare and socio-economic transformation processes take place more quickly. (d) Implementation of the program have not been able to reach the poor, the more helpless; power transfer does not occur, because the program is more utilized by the community group that is more capable and influential; (e) the empowerment program in poverty reduction is influenced by the strength of social capital is raised by a number of values (composite) that form a network of mutual trust, mutual respect and mutual benefit.The recommendations can be given: (a) strengthening of social capital shame / self-esteem, empathy, honesty, trust, altruism, visionary and rational to be an important note: while the mover of material progress is hard work and diligent, frugal, devoted to innovation , appreciate the work performance, visionary, and rational. The second joint values, namely for the strengthening of social capital on the one hand and to drive advances or capital reinforcement material on the other hand, together (synergistically) dibutuhan in the management of PEMP, P3EMDN Rural sustainable. (b) the empowerment of rural people especially the poor fishermen through the strengthening of social capital needs to be placed within the framework of the transformation or the development of sustainable rural communities (c) the development of coastal areas must pay attention to social relations in the fishing community, so as not to lead to social polarization. (c) factor of the village leadership, and extension workers to be important for the sustainability of an empowerment program in providing guidance for economically productive fishing communities in the form of technical development and business management. (d) to "coaching" post-program by the competent agency; (e) the need to empower the poor through increased coordination among agencies to reduce poverty.